Alevist politics of place and the construction of cemevis in Turkey - Es, Murat. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2006., 2006)
This thesis investigates some aspects of the reinstitutionalization process that the Alevi identity has gone through in the post-1980 period by focusing on the emergence of cemevis (houses of gathering) in urban public space. I look at various processes such as the displacement of Alevi communities to urban centers, the advent of a unitary signifier of Alevism, and the development of a new governmentality targeting the Alevi population by the Turkish state, through which cemevis have become institutional sites that signify Alevism and serve as focus for Alevist mobilization. I gathered my data by combining fieldwork that involved participant observation, in-depth and semi structured interviews with the analysis of the published material on Alevism, Alevis and cemevis. The fieldwork mostly concentrated on the Alibeyköy and Okmeydanı Cemevis. In this thesis, I suggest that cemevis do not simply provide space for the realization of communal services, but also play an important role in the public representation of Alevism(s) as they serve the reification of certain practices as "proper" manifestations of Aleviness. In cemevis new institutional positions are becoming apparent and various Alevi beliefs and practices have been subject to restructuration in accordance with the novel institutional frameworks Alevi groups have encountered as a result of increasing interaction with various state agencies and the Sunni majority. My findings demonstrate that cemevis have been conducive to the organization of a secularized way of life for Alevis in combination with the development of a new Alevi religiosity practiced at the individual level.
Keywords: Bektashi.